QUALITY OF DOCUMENTATION IN VIDEOGRAPHICFORM IN THE 2019 INACRAFT EXHIBITION - Revonza, Hanida Vidadelya; Mustofa, Budiman Mahmud (UI Scholars Hub, 2019)
Documentation is an important thing in a company. One of the most influential documentation is documentation in the form of videography. The purpose of this study was to find out how the quality of videography as a form of documentation made by PT Mediatama Binakreasi at the 2019 Inacraft Exhibition. This research is a collection of qualitative data, methods of collecting observation data, and interviews with Moch Sobri as multimedia designers from PT Mediatama Binakreasi and Rizky as videographer from Numoto Photo. The results of this study provide knowledge that videography as a form of documentation made for the 2019 Inacraft Exhibition is quite good and satisfying. The data created and the video editing process are all compiled through by the existing documentation team.